The liquid identity of adolescents with disabilities: Changes in the identity of adolescents with disabilities in social media - Merlia Indah Prastiwi; Bagong Suyanto; Yuyun Wahyu Izzati (Masyarakat, Kebudayaan dan Politik, 2022)
Studies on liquid identity have been done by many previous researchers. However, this article sees it differently where liquid identity is experienced by adolescents with disabilities who basically have many difficulties, obstacles in interacting with society in general. This study aimed to look at the process, intention, and purpose of the liquid identity experienced by adolescents with disabilities on social media. This study used a virtual ethnographic method with informants who are members of the Facebook community named “Indonesian Association of People with Disabilities.” The number of informants is 23 adolescents with disabilities who are users of social media. The findings of this study showed that adolescents with disabilities take various ways to get recognition and acceptance by a wide audience according to their type and characteristics. This is done by using social media called liquid identity. To get recognition and acceptance on social media, the practice of liquid identity of adolescents with disabilities was shown by hiding their real identity, having multiple accounts, and sharing positive things on social media. This study concluded that support from various parties is needed, either from the community, parents, friends, schools, and the environment. The role of these parties is important to provide motivation, enthusiasm, and encouragement so that adolescents with disabilities can show value on social media with their identity that is recognized by the public as a positive identity.